On the precision population projections with reference to Libyan data - Dr.A.H.Azzam; Dr.M.Y.EL Bassiouni (Dirasat in Economics and Business, 1973)
Introduction population projection is a prediction of a random vector viable x which represents the population by age and sex in year t. for an illustration of the population projection for Libya, see Venkatacharya (1972), see also Appendix I). The population is assume med to be closed and to grow according to fixed schedules of birth and death probabilities. This can be viewed as a multi-type branching process (Schweder, 1971). There are three main causes for the deviations in the projection as pointed out by Schweder (1971), “ (a) The projection model is inadequate in that the dynamics of the population development is not correctly described by the given fixed schedules in all years 1, 2, ... , T. (b) Even if these schedules are constant throughout the projection period we should expect a deviation simply because we use their estimates. (c) Even if the model is adequate and the proper schedules are used we should still expect a non-vanishing deviation because the population development is stochastic and not deterministic in its nature.” Sykes (1969) has shown by a specific example that the branching process model does not account for any substantial part of the observed variability in the dynamics of actual populations, i.e.,